User Behavior in The Acceptance of Technology on Regional Management Information System (SIMDA-Integrated) in Surakarta City Government - Simon Nisja Putra Zai (International Journal of Seocology, 2021)
This study aims to analyze aspects of the implementation of technology acceptance (SIMDA-integrated) in the surakarta city government. this study involved 6 participants in various areas of system users in surakarta city government, namely the department of communication, information, and security services; regional development planning, and research agencies; development administration and civil registry service. Qualitative data obtained research through interviews and observations to compile code, then build themes, and concepts about behavior. This study found that behavior regarding service quality, affective power, easy of use and usefulness is the reason employees use technology consistently. This study also found that inclusive attitudes, perceptions about system efficiency, the ability of employees to innovate, are means of building user awareness about the utilization of e-government in creating good governance. This study found that accountability is the impact of the intention of using the system, the intention of users in providing recommendations to other users, as well as the level of user awareness about the importance of e-government. Novelty produced in this study is about the model of measuring government accountability based on the behavior of system users in adopting the new system. Researcher provides recommendations on the importance of conducting periodic mentoring, training and socialization consistently, as well as increasing the intensity of the monitoring and evaluation process.